DIVIDEND POLICY AND MARKET BEHAVIOR: EVIDENCE FROM INDONESIA - Christian Hosea Immanuel; Cicilia Erna Susilawati (Widya Mandala Surabaya Catholic University, 2026)
Research Purposes. This study investigates the effect of market behavior on dividend policy within the Catering Theory framework, where market conditions reflect underlying investor sentiment. In this study, market behavior is captured through proxies, namely, unexplained market behavior and abnormal trading volume. Research Methods. Using a quantitative causal research design, this study examines secondary data derived from annual reports and market data of listed firms during the 2020–2024 period, with the change in dividend payout ratio serving as the dependent variable, free cash flow, Debt, and net income included as control variables and multiple regression analysis applied to test the proposed hypotheses. Research Results and Findings. The findings indicate that unexplained market behavior and abnormal trading volume have a positive and significant effect on changes in the dividend payout ratio. At the same time, free cash flow also shows a significant influence, whereas Debt and net income do not. These results suggest that corporate dividend decisions in Indonesia are driven not only by firm fundamentals but also by market preferences and behavioral factors as explained by the Catering Theory. This study implies that dividend policy should consider both firm fundamentals and market conditions in corporate decision-making.